The gender disaggregated database information system (GDDIS) / Viniita K.K.Vasu - Viniita, K.K.Vasu (2003)
The Gender Disaggregated Database Information System (GDDIS) is basically a system, which makes the process of viewing data collected from a census faster and easier for the users. GDDIS is intended to provide a computer-based system for census information. Besides that, GDDIS provides a user-friendly application. Users are able to access to GDDIS at anytime of the day. Primarily, the system would process and compute the total on the information provided to a specific census indicator. The system would then provide the facility of printing the completed information. Besides providing these functions, the users of GDDIS are also able to view the output in the form of a table, chart or graph. GDDIS consists of two modules. First, which is the user module, provides the facility of accessing and retrieving the required information, analyzing the information, presenting the data in a raphical output, printing the required information and changing the password. The second module is the administrator module, which enables the administrator to modify the database records, add new users, changing administrator password and transferring data for archiving. The system is expected to save time as the information gathered from a census that has been carried out is keyed into the database on a timely basis and this prevents the user from searching for the latest information. The information from the is secured as the data and information are kept in a database that is effective and efficient. GDDIS is to be developed using Microsoft Visual Basic 6.0, Microsoft SQL Server and SPSS Statistical Package. Microsoft Visual Basic 6.0 is used to create user friendly interface, Microsoft SQL Server is for storing information in database while SPSS is for the generation of tables, graphs and charts. All three works well when integrated ..